Ion‐Pairing Assemblies of Porphyrin–AuIII Complexes in Combination with π‐Electronic Receptor–Anion Complexes. Issue 4 (28th January 2020) - Tanaka, Hiroki; Haketa, Yohei; Bando, Yuya; Yamakado, Ryohei; Yasuda, Nobuhiro; Maeda, Hiromitsu
Abstract: Anion complexes of anion‐responsive π‐electronic molecules can behave as pseudo π‐electronic anions providing various ion pairs in combination with countercations. In this study, single crystals of ion‐pairing assemblies comprising porphyrin–Au III complexes and Cl − complexes of dipyrrolyldiketone BF2 complexes were prepared from 1:1 mixtures of anion receptors and the Cl − salts of cationic porphyrins in solution. In the solid state, the ion pairs formed characteristic assemblies, depending on the substituents of the anion receptors and porphyrin–Au III complexes. Theoretical calculations on the ion pairs revealed that the stacking structures are stabilized by compensating positive and negative charges as well as π–π interactions. Abstract : Ion‐pairing assemblies of porphyrin–Au III complexes and Cl − complexes of dipyrrolyldiketone BF2 complexes were formed in single crystals. In the solid state, the ion pairs formed characteristic assemblies determined by the substituents of the anion receptors and porphyrin–Au III complexes. Theoretical studies suggest that essential factors for the formation of the solid‐state ion‐pairing assemblies include charge compensation and π–π interactions.